Again and again : a novel - Evison, Jonathan (Dutton, 2023)
"Geno is living out his final days in a nursing home, bored, curmudgeonly, and struggling to connect with his nursing assistant, Angel, who he sees as being different from him in every way possible, and unable to understand him in any way. Perhaps no one really can, since Geno has been telling everyone who will listen that he's not just Geno--in fact, he's lived many past lives, dating back 1000 years, and since that first life in Seville, Spain, he has been searching for the love of his life he met then and only one other time since. Is this possible--was his life a miraculous one that let him live, again and again? Or is he crazy, or lonely, rehearsing larger-than-life fantasies to get through the day? As Angel comes to learn the truth about Geno, so do we, and as Geno's story comes to a head so does the biggest truth of all: that his story is an expansive ode to love--love we have had and lost, love we wish we had but didn't, and the love that might be staring us right in the face, that we don't even know we're lucky enough to have"--